2019
DOI: 10.1186/s12879-019-4540-z
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian modeling of spatiotemporal patterns of TB-HIV co-infection risk in Kenya

Abstract: BackgroundTuberculosis (TB) and Human Immunodeficiency Virus (HIV) diseases are globally acknowledged as a public health challenge that exhibits adverse bidirectional relations due to the co-epidemic overlap. To understand the co-infection burden we used the case notification data to generate spatiotemporal maps that described the distribution and exposure hypotheses for further epidemiologic investigations in areas with unusual case notification levels.MethodsWe analyzed the TB and TB-HIV case notification da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 42 publications
4
19
0
1
Order By: Relevance
“…Studies conducted in Ethiopia have shown that TB/HIV co-infected individuals have a greater risk of psychosocial problems, low quality of life, and poorer physical health than HIV infected individuals without active TB [1113]. The prevalence of TB/HIV co-infection has been found to vary widely in Ethiopia [14, 15] and other countries [1618], partially because of differences in health care access and other socio-demographic factors such as wealth index and literacy rate.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Ethiopia have shown that TB/HIV co-infected individuals have a greater risk of psychosocial problems, low quality of life, and poorer physical health than HIV infected individuals without active TB [1113]. The prevalence of TB/HIV co-infection has been found to vary widely in Ethiopia [14, 15] and other countries [1618], partially because of differences in health care access and other socio-demographic factors such as wealth index and literacy rate.…”
Section: Introductionmentioning
confidence: 99%
“…17 Bayesian modeling framework combines the likelihood function for the data and the prior distributions for the parameters resulting in a distribution known as the posterior distribution. 15,[17][18][19] The posterior distribution is defined as P θjy ð Þ, (i.e. probability distribution of the parameters given that the data which is proportional to the product of the likelihood function) while the prior distribution is defined as:…”
Section: Hierarchical Space Modelmentioning
confidence: 99%
“…Hence, the purpose of this study was to model the spatiotemporal risk pattern of TB in Ghana, using Bayesian hierarchical and space-time models discussed in previous literature. [12][13][14][15][16]…”
Section: Introductionmentioning
confidence: 99%
“…Kenya suffers from the dual epidemics ranking 4 th and 15 th globally in the high disease burden for HIV and TB respectively [31][32][33]. In 2013, Kenya reported more than 35% of the notified TB to be HIV infected compared to the global 13%.…”
Section: Plos Onementioning
confidence: 99%